2022
DOI: 10.3390/polym14020306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Granite Waste Powder by Varying the Molarity of Activator on the Mechanical Properties of Ground Granulated Blast-Furnace Slag-Based Geopolymer Concrete

Abstract: Industrial waste such as Ground Granulated Blast-Furnace Slag (GGBS) and Granite Waste Powder (GWP) is available in huge quantities in several states of India. These ingredients have no recognized application and are usually shed in landfills. This process and these materials are sources of severe environmental pollution. This industrial waste has been utilized as a binder for geopolymers, which is our primary focus. This paper presents the investigation of the optimum percentage of granite waste powder as a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 66 publications
(112 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, in the case of geopolymers based on ground granulated blast furnace slag, the addition of 20 % granite allows for a flexural strength of 4.89 MPa. However, when the additive is used in the amount of 10 % and 30 %, the bending strength is lower, which correlates with the results obtained by the authors [31]. Analyzing the discussed cases, it can be concluded that when designing geopolymers with the addition of granite, it is necessary to take into account not only the type of base material but also the share of the additive in the mixture, because these factors will significantly affect the final strength properties of the printed geopolymers.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, in the case of geopolymers based on ground granulated blast furnace slag, the addition of 20 % granite allows for a flexural strength of 4.89 MPa. However, when the additive is used in the amount of 10 % and 30 %, the bending strength is lower, which correlates with the results obtained by the authors [31]. Analyzing the discussed cases, it can be concluded that when designing geopolymers with the addition of granite, it is necessary to take into account not only the type of base material but also the share of the additive in the mixture, because these factors will significantly affect the final strength properties of the printed geopolymers.…”
Section: Resultssupporting
confidence: 89%
“…The selection of the appropriate amount of granite to achieve favorable strength properties will largely depend on the used base material. Thus, for example, in the case of geopolymer concretes based on ground granulated blast furnace slag, the addition of 20 % granite waste powder turns out to be the optimal amount, allowing a significant improvement in the compressive strength of geopol4ymers, below and above which significantly worse results are obtained [31].…”
Section: Resultsmentioning
confidence: 99%
“…an increase of 5% compared with the control concrete at a substitution rate of 40%. This increase in porosity is due to the presence of fines in the granite and additional porosity at the Interfacial Transition Zone (ITZ) between the smooth faces of the granite grains and the cement matrix [46]. On the other hand, there was a reduction in porosity when ordinary sand was replaced by recycled clinker sand.…”
Section: Porosity Accessible To Watermentioning
confidence: 99%
“…However, despite of its many advantages, GPC also has several drawbacks that need to be addressed. One of the major drawbacks is the relatively higher cost of production compared to traditional cement concrete [18]. The cost of production is mainly due to the high cost of the alkaline activator solution for the geopolymerization process [19].…”
Section: Introductionmentioning
confidence: 99%
“…GPC has a shorter working time, which can make it challenging to cast complex shapes or structures. In addition, the high viscosity of the geopolymer binder can lead to segregation and bleeding of the mixture, which can compromise the mechanical properties of the final product [18].…”
Section: Introductionmentioning
confidence: 99%